PENINGKATAN PRESTASI BELAJAR MAHASISWA PADA MATA KOMPUTER PEMROGRAMAN MELALUI PEMANFAATAN RECORDING MACRO - Tiwan Tiwan (Jurnal Pendidikan Teknologi dan Kejuruan, 2012)
ABSTRACTThe learning process of computer programming course requires the skills of programming flow arrangementand programming logic. The reading materials, exercises, and classroom discussion have not met the learninggoals of this course. Therefore, an additional media needs to be implemented to improve the learning process. Theprogram of macro recording in Microsoft Office can facilitate the students to have exercises and material analysisautonomously beyond the classroom activities.This study belongs to action research. The participants were the sixth semester students of Civil Engineeringand Planning, Faculty of Engineering, Yogyakarta State University, who joined computer programming course for4 months. This research employed two cycles, which was started by planning, implementation observation andfinally, reflection.The result of the research showed that there was an improvement of the learning achievement from 2.8 into3.29 for computer programming course by utilizing macro recording facility of Microsoft product.Keywords: Recording Macro, Learning Process